Artificial Intelligence: Revolutionizing the Future of Retail - Devarapalli, Chakradhar Avinash (Journal of Global Economy, Business and Finance, 2025)
Artificial Intelligence (AI) is revolutionizing the retail sector, catalyzing unprecedented advancements in operational efficiency, customer engagement, and strategic decision-making. This paper delves into the transformative impact of AI across the retail value chain, from inventory management and supply chain optimization to personalized customer experiences and dynamic pricing models. By leveraging AI-driven algorithms and machine learning techniques, retailers are not merely adapting to the rapidly evolving market dynamics but are actively shaping the future of retail. The integration of AI technologies, such as predictive analytics, natural language processing, and computer vision, enables retailers to achieve real-time insights and hyper-personalization, thereby enhancing customer satisfaction and loyalty. These technologies facilitate precise demand forecasting, automated inventory replenishment, and the optimization of logistics, reducing costs and minimizing waste. Furthermore, AI-powered recommendation engines and chatbots are redefining customer interaction by delivering tailored shopping experiences, fostering deeper connections between consumers and brands. This paper also examines the strategic implications of AI adoption in retail, highlighting its role in driving innovation and competitive advantage. Retailers that successfully harness AI capabilities are better equipped to anticipate customer preferences, respond to market trends, and create differentiated value propositions. Moreover, the ethical considerations surrounding AI deployment, including data privacy and algorithmic bias, are critically assessed to ensure responsible and sustainable AI integration. This study underscores the pivotal role of AI in propelling the retail industry toward a future characterized by enhanced efficiency, agility, and customer-centricity. By embracing AI, retailers are not only navigating the complexities of the digital age but are also setting new standards for operational excellence and customer engagement. The findings of this research provide valuable insights for retail practitioners, policymakers, and scholars, offering a comprehensive understanding of how AI is transforming the retail landscape and what it entails for the future of the industry.